Math skill enhancement patterns Theoretical research - كاطم, م.امیر جواد كاطم راضي (Sulaimani Journal for Humanities, 2025)
This study addresses the importance of mathematics as a fundamental science in our daily lives, where it plays a vital role in various scientific and artistic fields. Mathematics is considered more than just a collection of numbers and equations; it is a universal language used in various forms of advancement, from natural sciences and engineering to the arts. Many students struggle with learning mathematics, which negatively impacts their self-confidence and academic performance. Therefore, this research aims to explore new methods and approaches for effectively teaching mathematics and enhancing critical thinking and problem-solving skills among students. Researchers conducted a comprehensive study on the methods of teaching mathematics used in schools, focusing on modern and innovative techniques. They analyzed students' experiences and opinions regarding different educational approaches, in addition to evaluating the effectiveness of these methods in improving understanding and performance levels. Surveys and interviews with teachers and students were used to gather the necessary data. The results showed that having a well-structured educational plan is fundamental to achieving learning objectives. It also demonstrated that active student participation in educational activities enhances their experience in learning mathematics. The new approaches helped change students' expectations towards mathematics, leading to improved performance. The results also emphasized the importance of continuous assessment as a means to identify students' specific needs and provide appropriate support. The study revealed a positive relationship between teachers and students, contributing to a supportive and encouraging educational environment. The findings of this research confirm the necessity of developing teaching methods in mathematics to meet students' needs and enhance their self-confidence, thereby improving their academic performance and reinforcing the status of mathematics as a fundamental science in education
Keywords: Mathematics Education; Innovative Teaching Methods; Enhancing Critical Thinking